Application of Mahalanobis-Taguchi System in Liver Function Profile of Methadone Flexi Dispensing Program - S. N. A. M., Zaini; S. K. M. Saad; M. Y., Abu (UNIMAS Publisher, 2022)
Patients under the methadone flexi dispensing (MFlex) program are required to do blood tests like liver function profile. A doctor assesses 3 parameters like Alk phosphatase, ALT (SGPT), and AST (SGOT) to ensure the patient has a liver problem. Consequently, the existing system does not have a stable ecosystem towards classification and optimization. The objective is to apply the Mahalanobis-Taguchi system (MTS) in the MFlex program. The data is collected at Bandar Pekan clinic with 34 parameters. Two types of MTS methods are used like RT-Method and T-Method for classification and optimization respectively. The average Mahalanobis distance (MD) of healthy is 1.00 and unhealthy is 352.58. A positive degree of contribution has only 1 parameter. 15 unknown samples have been diagnosed. Type 2 of 6 modifications has been selected as the best-proposed solution. In conclusion, a pharmacist from Bandar Pekan clinic confirmed that MTS is able to solve problems in the classification and optimization of the MFlex program.